Plasma B-type natriuretic peptide concentration for diagnosis of acute heart failure with renal insufficiency (Bangabandhu Sheikh Mujib Medical University Journal, 2016)
Background : Plasma B-type natriuretic peptide (BNP) is the diagnostic tool for acute heart failure (AHF).This natriuretic peptide level depends on renal function, through renal metabolism and excretion. Therefore we examined the effect ofrenal impairment on plasma BNP level during diagnosis of AHF.Objective: The objective of the study was to assess the effect of renal dysfunction on plasma BNP level and to determine appropriate cutoff value of plasma BNP to diagnose the patients of AHF with renal insufficiency.Methods: This cross sectional analytical study was conducted in the Department of Biochemistry Bangabandhu Sheikh Mujib Medical University (BSMMU). The study was done among 90 AHF patients selected from cardiology emergency department during the period of July 2012 to June 2013. After enrollment plasma BNP concentration was measured and eGFR was estimated from serum creatinine by the four parameter Modification of Diet and Renal Disease (MORD) equation and then grouped into two groups on the basis of empirical cut off value of eGFR 60 ml/min/1.73 m2Results: In this study a significant negative correlation was found between plasma BNP evel and eGFR (P